Characterizing Boron-Enhanced One-Part Alkaline-Activated Mortars: Mechanical Properties, Microstructure and Environmental Impacts - Orklemez, Ezgi; Ilkentapar, Serhan; Durak, Ugur; Gulcimen, Sedat; Uzal, Nigmet; Uzal, Burak; Atis, Cengiz Duran (Elsevier Sci Ltd, 2024)
Since alkali activators negatively effect the environmental impact assessment, it is necessary to develop the alternative activators from natural sources with low environmental impact. Therefore, in this study, the usage of boron refined products colemanite, ulexite and boron pentahydrate as activators in slag-based alkali-activated mortar systems was investigated in detail. Flexural and compressive strength tests, isothermal calorimetry measurement, thermogravimetric and differential thermal analysis, inductively coupled plasma mass spectrometry analysis, field emission scanning electron microscopy, and energy dispersive analysis and elemental mapping and X-ray diffraction analysis were carried out on the samples. In addition, sample production was subjected to life cycle analysis (LCA) with a cradle-to-gate approach using two different transportation scenarios. According to the results obtained, it was determined that colemanite, ulexite and boron penta hydrate, when used in optimum proportions, had a positive effect on strength (up to increase 40% compressive strength by 20% ulexite replacement) and could be used as an activator in slag-based alkali-activated systems. The positive results obtained in strength as a result of using boron-refined products are also supported by other test results conducted within the scope of the study. Furthermore, according to the LCA results, it was observed that there was a significant decrease in global warming potential with the substitution of 20% colemanite, ulexite or boron pentahydrate as activators, not only compared to the reference sample but also traditional cementitious systems.
Orklemez, Ezgi/0000-0003-0514-7370;
Keywords: Alkali -Activated System; Slag; Boron Refined Product; Life Cycle Assessment; Alkali-Activated System